Механизмы термической и термоокислительной деструкции полиэтилентерефталата - Kongapshev A. A., Binogerova F. A. (Education and science in the modern context, 2017)
This work is devoted to study of the mechanisms of breakdown of polybutylene terephthalate at high temperatures, as well as the mechanisms of splitting PBTF in a joint action of temperature and oxygen. Described in the form of reactions all stages of cleavage of the polybutylene terephthalate. The process of thermooxidative degradation PBTF flows through pseudomona- (if formed peroxide radicals) or bimolecular (if formed hydroperoxides) decomposition.
Keywords: полибутилентерефталат; термическая деструкция; термоокислительная деструкция; polybutylene terephthalate; thermal degradation; thermal oxidative degradation